2022
DOI: 10.1017/s0954579422001146
|View full text |Cite
|
Sign up to set email alerts
|

Childhood sexual abuse and pervasive problems across multiple life domains: Findings from a five-decade study

Abstract: The aim of this study was to use longitudinal population-based data to examine the associations between childhood sexual abuse (CSA) and risk for adverse outcomes in multiple life domains across adulthood. In 937 individuals followed from birth to age 45y, we assessed associations between CSA (retrospectively reported at age 26y) and the experience of 22 adverse outcomes in seven domains (physical, mental, sexual, interpersonal, economic, antisocial, multi-domain) from young adulthood to midlife (26 to 45y). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…Sexual abuse was statistically associated with a lifetime diagnosis of psychiatric disorders, including anxiety disorder, depression, eating disorders, posttraumatic stress disorder, sleep disorders, and suicide attempts, according to meta-analysis and longitudinal study. 65 , 66 A higher probability of exhibiting symptoms consistent with severe depression was found in individuals whose sexual abuse took place prior to the age of twelve, according to a study by Schoedl et al 67 Adams et al 68 discovered that, unlike during childhood and adolescence, a prior history of sexual abuse prior to the age of six did not exhibit a significant predictive effect on psychopathology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sexual abuse was statistically associated with a lifetime diagnosis of psychiatric disorders, including anxiety disorder, depression, eating disorders, posttraumatic stress disorder, sleep disorders, and suicide attempts, according to meta-analysis and longitudinal study. 65 , 66 A higher probability of exhibiting symptoms consistent with severe depression was found in individuals whose sexual abuse took place prior to the age of twelve, according to a study by Schoedl et al 67 Adams et al 68 discovered that, unlike during childhood and adolescence, a prior history of sexual abuse prior to the age of six did not exhibit a significant predictive effect on psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…The potential impact of sexual abuse on neurocognitive function could be accounted for by the known cognitive function-altering effects of ACEs on various pathways, such as inflammation, 66 , 88 , 97 alterations in the HPA-axis, 97 and disruptions in the cortical and subcortical regions. 98 Likewise, NLEs have a plethora of detrimental effects on the same pathways, including the IRS, 99 , 100 oxidative stress pathways, 101 HPA-axis function, 102 and methylation processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two meta-analyses revealed that childhood SA is estimated at 18% for girls and 7.9% for boys (Pereda et al, 2009; Stoltenborgh et al, 2011) while lifetime SA is estimated at as high as 23% for men and 37% for women (Chiu et al, 2013; Smith et al, 2018). There is extensive literature that shows that SA increases an individual’s vulnerability to a range of physical, psychological, and behavioral impairments (Atabay & Arman, 2019; Gladstone et al, 2004; Guiney et al, 2022; Kendall-Tackett et al, 1993; Lang et al, 2004; Lo Iacono et al, 2021) and that childhood SA is a key risk factor in the development of psychiatric disorders in adulthood (Read, 1997; Wurr & Partridge, 1996).…”
Section: Sexual Abuse (Sa)mentioning
confidence: 99%
“…PTSD in children and adolescents -often referred to as pediatric PTSD -is a common, impairing 4 , and often chronic 10 mental disorder characterized by vivid re-experiencing of the trauma (e.g., intrusions or nightmares), avoidance of trauma-related situations, thoughts, and emotions, lasting changes in cognitions (e.g., self-blame) and emotions (e.g., shame), as well as hyperarousal symptoms (e.g., hypervigilance) 11 . Given its high prevalence and chronicity, pediatric PTSD, if left untreated, is a substantial burden to the individual and society [12][13][14][15] . Particularly during sensitive developmental periods in childhood and adolescence, unaddressed PTSD can disrupt crucial developmental processes 16 .…”
mentioning
confidence: 99%